Novel Method for Implantation of Balloon Expandable Transcatheter Aortic Valve Replacement to Reduce Pacemaker Rate—Line of Lucency Method. Issue 5 (2nd September 2020) - Ramanathan, P. Kasi; Nazir, Salik; Elzanaty, Ahmed M.; Nesheiwat, Zeid; Mahmood, Muhammad; Rachwal, William; Riordan, Christopher; Letcher, John; Yenrick, Kellie; Boonie, Erica; Moront, Michael G.; Redfern, Roberta E.; et al.
ABSTRACT: Background: The risk of permanent pacemaker implantation (PPM) following transcatheter aortic valve replacement (TAVR) remains high. Valve implantation depth is an independent predictor of PPM. This study describes the rate of PPM following a novel method for valve positioning during TAVR. Methods: A retrospective cohort study involved patients undergoing TAVR at our institute between January 2019 and January 2020. Baseline characteristics, procedural data, and clinical outcomes were collected and analyzed. All patients were implanted with the Edwards SAPIEN 3 or SAPIEN 3 Ultra using the radiolucent line on the stented valve, rather than the central marker, to guide positioning. We describe this as the line of lucency method. Results: In total, 50 patients (96% SAPIEN 3, and 4% SAPIEN 3 Ultra) were included. The median age was 81.5 years, and 30 (60%) patients had existing conduction abnormalities: first degree atrio-ventricular block (18%), right bundle branch block (12%), left bundle branch block (10.2%), and left anterior fascicular block (16%). The modified technique was successful in all cases. No patient required PPM within 30 days. Two patients (4%) had moderate aortic regurgitation on echocardiogram at 30 days; 3 (6%) developed new left bundle branch block. There was no instance of valve embolization, coronary obstruction, or postprocedural death. Conclusion: A novel technique utilizing the radiolucent line on the bottom of the stented valve during TAVR provided reproducibly high positioning with excellent clinical results. Optimal position of the valve may prevent need for subsequent PPM.